HP1-DRIVEN MICRO-PHASE SEPARATION OF HETEROCHROMATIN-LIKE DOMAINS/COMPLEXES - Singh, Prim B.; Newman, Andrew G. (Epigenetics Insights ﻿, 2022)
Cytologically visible constitutive heterochromatin found at the centromeric and telomeric regions of chromosomes represents the largest differentiated chromatin compartment in eukaryotic nuclei.1 Outside constitutive heterochromatin, heterochromatin- like domains (HLD, >.1 Mb) and complexes (HLC, <.1 Mb) are found along the chromosome arms.2 HLD/Cs are present in eukaryotic genomes as divergent as fission yeast and human, with expansions in size and number in mammals. In human, there are ~163 to 859 HLDs and ~18 853 to 32 292 HLCs, depending on cell type.2 Some of the largest HLDs are the KRAB-ZNF HLDs on chromosome 19. Notably, contacts among these large HLDs emerge as the heterochromatic B4 sub-compartment in Hi-C maps...
Keywords: Type of access: Open Access; Heterochromatin; HP1; Hi-C; H3K9me3; phase separation